1998
DOI: 10.1103/physrevc.57.3340
|View full text |Cite
|
Sign up to set email alerts
|

ddibaryon in a colored cluster model

Abstract: The mass and wave function of a six-quark system with quantum numbers J P =0 − , T=0, called d ′ , are calculated. We use a colored diquark-tetraquark cluster model for the six-quark wave function. A constituent quark model Hamiltonian with a two-body confinement potential, and residual one-gluon, one-pion, and one-sigma exchange interactions is used. The complications due to the quark exchange interactions between tetraquark and diquark clusters (Pauli principle) are taken into account within the framework of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…A worldwide theoretical and experimental effort to search for dibaryon states with and without strangeness lasts for a long time. The S = 0, J P = 0 − d ′ dibaryon, which is hard to be explained by quark models [4], was claimed by experiments in 1993 and disappeared years later [5]. Our group showed that the S = 0, I = 0, J = 3 d * is a tightly bound sixquark system rather than a loosely bound nucleus-like system of two ∆s [6][7][8][9].…”
Section: Introductionmentioning
confidence: 84%
“…A worldwide theoretical and experimental effort to search for dibaryon states with and without strangeness lasts for a long time. The S = 0, J P = 0 − d ′ dibaryon, which is hard to be explained by quark models [4], was claimed by experiments in 1993 and disappeared years later [5]. Our group showed that the S = 0, I = 0, J = 3 d * is a tightly bound sixquark system rather than a loosely bound nucleus-like system of two ∆s [6][7][8][9].…”
Section: Introductionmentioning
confidence: 84%
“…[7]. Recently, the proposed d ′ (IJ P = 00 − ) dibaryon has been studied by Faessler's group [8] , who concluded that both bag and hybrid meson-gluon exchange models cannot obtain such a state with a mass as low as 2.06GeV. If the d ′ is proven to exist, that will argue strongly against the completeness of these models.…”
Section: Introductionmentioning
confidence: 99%
“…The possible existence of unstable non-strange two-and three-baryon resonances corresponding to bound-state solutions of systems composed of nucleons and deltas has been speculated for years [217][218][219][220][221][222][223][224][225][226]. In the case of two-body systems (that we shall refer to as dibaryons) they will decay mainly into two nucleons and either one or two pions, while for the three-body case (tribaryons) they will decay mainly into three nucleons and either one, two, or three pions.…”
Section: Dibaryons and Tribaryonsmentioning
confidence: 99%